Vaccine-induced CD8 T cells are redirected with peptide-MHC class I-IgG antibody fusion proteins to eliminate tumor cells in vivo. Issue 1 (1st January 2020) - Fischer, Cornelia; Munks, Michael W.; Hill, Ann B.; Kroczek, Richard A.; Bissinger, Stefan; Brand, Verena; Schmittnaegel, Martina; Imhof-Jung, Sabine; Hoffmann, Eike; Herting, Frank; Klein, Christian; Knoetgen, Hendrik
ABSTRACT: Simulating a viral infection in tumor cells is an attractive concept to eliminate tumor cells. We previously reported the molecular design and the in vitro potency of recombinant monoclonal antibodies fused to a virus-derived peptide MHC class I complex that bypass the peptide processing and MHC loading pathway and directly displays a viral peptide in an MHC class I complex on the tumor cell surface. Here, we show that a vaccination-induced single peptide-specific CD8 T cell response was sufficient to eliminate B16 melanoma tumor cells in vivo in a fully immunocompetent, syngeneic mouse tumor model when mice were treated with mouse pMHCI-IgGs fusion proteins targeting the mouse fibroblast activation protein. Tumor growth of small, established B16 lung metastases could be controlled. The pMHCI-IgG had similar potency as an analogous pan-CD3 T-cell bispecific antibody. In contrast to growth control of small tumors, none of the compounds controlled larger solid tumors of MC38 cancer cells, despite penetration of pMHCI-IgGs into the tumor tissue and clear attraction and activation of antigen-specific CD8 T cells inside the tumor. pMHCI-IgG can have a similar potency as classical pan-T-cell recruiting molecules. The results also highlight the need to better understand immune suppression in advanced solid tumors.